(untitled) (Nigerian Journal of Technology, 2017)
The power output of a spark ignition engine could be improved by boosting the intake pressure and compression ratio; however the applications of these are limited by knock in engines. This study examined the knocking behaviours of three commercially available fuels for spark ignition engines operated at engine intake pressures of 1.6 and 2.0 bar. The pressure data for the fuels tested were grouped into three: the fast cycle, medium cycle and slow cycles. Knock intensities from the pressure data were processed with Fast Fourier Transform (FFT) and band pass filtering techniques. The results showed that the knocking cycles occurred only in the fast and medium cycles. These results supported the view that auto-ignition of end-gases was due to compression from the high speed propagating flames. FTiR spectrums showed that the presence of aromatics was responsible for the better anti-knock quality exhibited by E5 and ULG 98 over PRF 95. http://dx.doi.org/10.4314/njt.v36i2.25